AN APPRAISAL OF SAFETY OF TRACTOR-TRAILER - O. A. Ogunjirin; A. O. Ogunlela (Nigerian Journal of Technological Development, 2011)
The tractor-trailer braking system was appraised considering the effect of braking the tractor or trailer alone and also braking the combination of tractor and trailer simultaneously. The study became imperative considering the influx of trailers that are not equipped with the braking system and the danger it poses to the operators and the farm produce. The study employed simple field simulation of the behaviour of each model and further analysis of the system. The result showed that it would be in the best interest of any country importing agricultural trailers to import those equipped with braking system which could be actuated by the hydraulic control of the tractor. This would reduce to the barest minimum dangers associated with operators of tractor-trailer systems, tyres and loss or damage to produce being transported.